Content updating method in FemtoCaching - Apipong Pingyod (2018)
Work in FemtoCaching proposes the algorithm to place contents in caches of femto-cells but it does not consider changes of content ranking and content popularities. However, content ranking and content popularities change during time. Therefore, the caches should be updated. In addition, the number of contents to be updated should be limited. In this research, we propose a method to update contents in caches of femto-cells in FemtoCaching. The proposed method has a complexity less than the contents placement algorithm of FemtoCaching. The performance of proposed method is evaluated by a simulation. The experimental results show that the proposed method has an acceptable performance. © 2014 IEEE.